2019
DOI: 10.1108/jmd-11-2018-0331
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effects of product innovation in relation between knowledge management and competitive advantage

Abstract: Purpose The purpose of this paper is to examine the mediating effect of product innovation on the relation between the knowledge management and competitive advantage. To analyze the effect of knowledge management on innovation, the effect of knowledge management on competitive advantage and the effect of innovation on competitive advantage in small and medium enterprises in food products are taken into account. Design/methodology/approach The approach used in this study was quantitative approach. The populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 41 publications
1
30
0
2
Order By: Relevance
“…Results using Sobel's test (Sobel 1982) for a better interpretation of the mediating effect, as applied by Clarke and Rhodes (2020) and Wahyono (2019), to test the statistical significance of the indirect effects, confirmed that ESE has a significant indirect impact on IB through EP (Table 8). In other words, ESE's impact on IB is mediated by EP.…”
Section: Evaluation Of the Structural Modelmentioning
confidence: 68%
See 1 more Smart Citation
“…Results using Sobel's test (Sobel 1982) for a better interpretation of the mediating effect, as applied by Clarke and Rhodes (2020) and Wahyono (2019), to test the statistical significance of the indirect effects, confirmed that ESE has a significant indirect impact on IB through EP (Table 8). In other words, ESE's impact on IB is mediated by EP.…”
Section: Evaluation Of the Structural Modelmentioning
confidence: 68%
“…Several scholars have researched the topic of innovation in recent years. Different studies (Balsmeir et al, 2017;Kogan et al, 2017;Ramírez-Montoya 2018;Coad et al, 2016;2019) analyze its implication in large and small companies, its importance as a business tool and its implication in the academy. Scott and Bruce (1994) identify a three-layer process of IB, explaining how an individual innovates in the workplace.…”
Section: Innovative Behavior (Ib)mentioning
confidence: 99%
“…Innovation capability is classified into many types such as product and process innovation (Tsai et al, 2001), exploitative and exploratory innovation (Than et al, 2021); innovation speed and quality (Le & Le, 2018), radical and incremental innovation (Nguyen et al, 2021), and frugal innovation capability (Le, 2021). This study focus on TL-innovation capability relationship in term of product innovation because innovation product is widely regarded as the main form of innovation capability Wahyono, 2019). Wherein, product innovation refers to organization's capability of providing differentiated or new products/services in the market to acquire customers' satisfaction Rasheed et al, 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Research on product innovation in manufacturing companies in Turkey was carried out by Aydin [9]. Other research in SMEs was conducted by Ko et al and Wahyono [10], [11]. Widya Hastuti et al [12] analyzed process innovation in SMEs [12].…”
Section: Literature Reviewmentioning
confidence: 99%